The prevalence of herpesvirus infections in children and young adults transplant recipients - kidney and hematopoetic stem cells - Markolović, Marina T; Ćupić, Maja (Medicinski podmladak, 2018)
Introduction: Viruses are the most important and common cause of opportunistic infections following transplantation. The risk correlates with the virus encountered, transplanted tissue and organ, intensity of immune suppression, and other host factors governing susceptibility. Infections caused by the human herpesviruses, continue to challenge the clinical management of transplant recipients. Aim: The aim of this study was to investigate the prevalence of herpesvirus infections among pediatric hematopoetic stem cell and renal transplant recipients (HSCTR and RTR). Material and methods: This is a retrospective study of 150 pediatric HSCTR and RTR investigated in plasma samples by PCR in multiple testings, on the presence of cytomegalovirus (CMV), Epstein–Barr virus (EBV), herpes simplex virus type 1 and 2 (HSV1/2) and human herpes virus 6 (HHV6) during 2015/2016 period. Visualization of PCR products was performed by electrophoresis on 2% agarose gel with ethidium bromide. For statistical analyses T test, McNemar’s test, Chi - square and Fisher’s exact test were used. Results: During 2015 statistical significance was reached at the follow ups, where 33.3% (p=0.031) and 46.7% (p=0.016) of HSCTR, and 4.3% and 28.0% of RTR, had positive CMV and EBV results, respectively, in regard to the first test. During 2016 similar finding was observed where HSCT recipients had 70.6% CMV (p=0.002) and 29.4% EBV positive results during the follow ups. CMV finding was negative in all RTR, but 12.5 and 4.0% of investigated kidney recipients were EBV positive during the first test and follow ups, respectively. Conclusion: The results demonstrated that HSCTR are in a greater risk of CMV and EBV infections, compared to RTR. Therefore, the importance of permanent post - transplant monitoring of herpesviruses is in timely diagnosis and prevention of overt infections from occurring. Keywords: herpesviruses, pediatric transplant recipients, HSCTR, RTR, post-transplant CMV monitoring, post-transplant EBV monitoring